2015
DOI: 10.1128/mcb.00503-14
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Mitogen-Activated Protein Kinase Phosphatase 1 Selectively Regulates Glucose Metabolism and Energy Homeostasis

Abstract: The liver plays a critical role in glucose metabolism and communicates with peripheral tissues to maintain energy homeostasis. Obesity and insulin resistance are highly associated with nonalcoholic fatty liver disease (NAFLD). However, the precise molecular details of NAFLD remain incomplete. The p38 mitogen-activated protein kinase (MAPK) and c-Jun NH 2 -terminal kinase (JNK) regulate liver metabolism. However, the physiological contribution of MAPK phosphatase 1 (MKP-1) as a nuclear antagonist of both p38 MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
100
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(107 citation statements)
references
References 46 publications
7
100
0
Order By: Relevance
“…In contrast to the studies by Vernia et al [22, 23], it has also been reported that p38α/β MAPK, rather than JNK, is involved in the regulation of FGF21 [25]. Mice lacking the expression of MKP-1 in the liver exhibit decreased levels of circulating FGF21 under conditions in which both hepatic p38α/β MAPK and JNK are elevated [25]. Activated mutants of the upstream MAPK kinases for JNK failed to have an effect on a minimal FGF21 promoter but rather a negative regulatory effect on p38α /β MAPK to control FGF21 through a PGC-1α-dependent pathway [25].…”
Section: Jnk In Hepatic Metabolism and Pathophysiologymentioning
confidence: 87%
See 4 more Smart Citations
“…In contrast to the studies by Vernia et al [22, 23], it has also been reported that p38α/β MAPK, rather than JNK, is involved in the regulation of FGF21 [25]. Mice lacking the expression of MKP-1 in the liver exhibit decreased levels of circulating FGF21 under conditions in which both hepatic p38α/β MAPK and JNK are elevated [25]. Activated mutants of the upstream MAPK kinases for JNK failed to have an effect on a minimal FGF21 promoter but rather a negative regulatory effect on p38α /β MAPK to control FGF21 through a PGC-1α-dependent pathway [25].…”
Section: Jnk In Hepatic Metabolism and Pathophysiologymentioning
confidence: 87%
“…Further evidence for a role for p38α/β MAPK in gluconeogenesis is derived from work studying MKP-1. MKP-1 liver-specific knockout mice exhibit enhanced G6pc and Pck1 , suggesting that MKP-1 negatively regulates gluconeogenesis by opposing p38α/β MAPK- and/or JNK-mediated activation of the gluconeogenic program [25]. These studies establish an important role for hepatic MKP-1 and hence the MAPKs in the regulation of gluconeogenesis (Table 3).…”
Section: P38 Mapk In Hepatic Metabolism and Pathophysiologymentioning
confidence: 99%
See 3 more Smart Citations